Analisis Strategi Komunikasi Dakwah Ikaba Dalam Meningkatkan Jaringan Alumni Ponpes Al-Ishlahuddiny Kediri Lombok Barat - Muhammad Ikhwan Fiddaraini Hasipa (STAI Bumi Silampari, 2025)
The transformation of da'wah in the digital era requires pesantren alumni organizations to design adaptive and sustainable communication strategies. This study analyzes the da'wah communication strategy of the Al-Ishlahuddiny Alumni Family Association (IKABA) in strengthening the alumni network of Al-Ishlahuddiny Islamic Boarding School in Kediri, West Lombok. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation. The results show three main strategies: empathy-based interpersonal communication, utilization of digital media such as WhatsApp and Instagram, and implementation of collective activities such as studies and webinars. These strategies effectively address the challenges of cross-generational communication and limited alumni participation. IKABA is able to build emotional networks and adapt pesantren values to the digital social space. This research contributes to the understanding of alumni-based community da'wah strategies and suggests comparative studies on similar communities to test the effectiveness of this model more broadly